catena-Poly[[[bis(3-aminopyrazine-2-carboxylato)triaquapraseodymium(III)]-μ-3-aminopyrazine-2-carboxylato-[(3-aminopyrazine-2-carboxylato)diaquaformatopraseodymium(III)]-μ-3-aminopyrazine-2-carboxylato] hexahydrate] - Gao, Shan (International Union of Crystallography, 2011)
The asymmetric unit of the polymeric title compound, {[Pr(2)(C(5)H(4)N(3)O(2))(5)(CHO(2))(H(2)O)(5)]·6H(2)O}(n), has two independent Pr(III) atoms; one is coordinated by two water molecules and the other by three water molecules. The first is N,O-chelated by three 3-aminopyrazine-2-carboxylate ions, whereas the second is chelated by two carboxylate ions; both exist in a monocapped square-antiprismatic geometry. The polymeric chains that run along the a axis interact with the lattice water molecules, generating a three-dimensional hydrogen-bonded network. The formate ion is disordered over two positions with respect to the non-coordinated atoms in a 1:1 ratio.